Dosimetry, Optimization and FMEA of Total Skin Electron Irradiation (TSEI) - Shariff, Maya; Stillkrieg, Willi; Lotter, Michael; Lohmann, Daniel; Weissmann, Thomas; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Total Skin Electron Irradiation (TSEI) is a method for treating malignant cutaneous T-cell lymphomas. This work aims to implement and optimize the total skin technique established at Strahlenklinik Erlangen, Germany on two new linear accelerators and to quantify the risks using failure mode and effects (FMEA) analysis. Material and methods: TSEI is performed at a VersaHD accelerator (Elekta, Stockholm) with 6 MeV in the “high dose rate mode” HDRE and a nominal field size of 40 × 40 cm2. To reach the entire skin surface, the patients perform 6 different body positions at a distance of 330 cm behind an acrylic scatter plate, with two overlapping irradiation fields being radiated at 2 gantry angles per position. The irradiation technique was commissioned according to the recommendation of AAPM report 23. With the help of a reference profile at 270°, 2 gantry angles were calculated, which in total resulted in an optimal dose distribution. This was metrologically verified with ion-chamber measurements in the patient's longitudinal axis. The influence of the shape of the acrylic scatter plate and the distance between the acrylic scatter plate and patient was determined by measurements. The dose homogeneity was verified using an anthropomorphic disc phantom equipped with GafChromic films. The workflows and failure modes of the total skin technique were described in a process map and subsequently quantified with a FMEA analysis. Results: An optimal dose distribution is achieved at a distance of SSD = 330 cm, using the gantry angles 289° and 251°. The previously used segmented acrylic scatter plate was replaced by a flat plate (200 × 120 × 0.5 cm3), which is placed at a distance of 50 cm in front of the patient. The densitometric evaluation of the GafChromic films in the anthropomorphic disc phantom revealed an expected dose distribution of 3 Gy at a depth of up to 1.5 cm below the skin surface, with a homogeneity of ±10% over the phantom's longitudinal axis. By FMEA a maximum risk priority number of 30 was determined. Conclusion: Based on the calculations and measurements performed on the new accelerators as well as the risk analysis, we concluded that total skin therapy can be implemented clinically.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Dosimetry; FMEA; HDRE; Mycosis fungoides; Quality assurance; Total Skin Electron Irradiation (TSEI)

End-to-end testing for stereotactic radiotherapy including the development of a MULTI-MODALITY phantom - Shariff, Maya; Grigo, Johanna; Masitho, Siti; Brandt, Tobias; Weiß, Alexander; Lambrecht, Ulrike; Stillkrieg, Willi; Lotter, Michael; Putz, Florian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: A new insert for a commercially available end-to-end test phantom was designed and in-house manufactured by 3D printing. Subsequently, the insert was tested for different stereotactic radiation therapy workflows (SRS, SBRT, FSRT, and Multimet) also in comparison to the original insert. Material and methods: Workflows contained imaging (MR, CT), treatment planning, positioning, and irradiation. Positioning accuracy was evaluated for non-coplanar x-ray, kV- and MV-CBCT systems, as well as surface guided radiation therapy. Dosimetric accuracy of the irradiation was measured with an ionization chamber at four different linear accelerators including dynamic tumor tracking for SBRT. Results: CT parameters of the insert were within the specification. For MR images, the new insert allowed quantitative analysis of the MR distortion. Positioning accuracy of the phantom with the new insert using the imaging systems of the different linacs was < 1 mm/degree also for MV-CBCT and a non-coplanar imaging system which caused > 3 mm deviation with the original insert. Deviation of point dose values was < 3% for SRS, FSRT, and SBRT for both inserts. For the Multimet plans deviations exceeded 10% because the ionization chamber was not positioned in each metastasis, but in the center of phantom and treatment plan. Conclusion: The in-house manufactured insert performed well in all steps of four stereotactic treatment end-to-end tests. Advantages over the commercially available alternative were seen for quantitative analysis of deformation correction in MR images, applicability for non-coplanar x-ray imaging, and dynamic tumor tracking.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Dynamic Tumor Tracking; End-to-End testing; MRI distortion; Quality Assurance; SBRT; SRS

German radiation oncology’s next generation: a web-based survey of young biologists, medical physicists, and physicians—from problems to solutions - Weissmann, Thomas; Deloch, Lisa; Grohmann, Maximilian; Trommer, Maike; Fabian, Alexander; Ehret, Felix; Stefanowicz, Sarah; Rühle, Alexander; Lettmaier, Sebastian; Putz, Florian; Shariff, Maya; Wegen, Simone; et al. (Strahlentherapie und Onkologie, 2024)
Background: Radiation science is of utmost significance not only due to its growing importance for clinical use, but also in everyday life such as in radiation protection questions. The expected increase in cancer incidence due to an aging population combined with technical advancements further implicates this importance and results in a higher need for sufficient highly educated and motivated personnel. Thus, factors preventing young scientists and medical personnel from entering or remaining in the field need to be identified. Methods: A web-based questionnaire with one general and three occupation-specific questionnaires for physicians, biologists, and medical physicists working in radiation oncology and research was developed and circulated for 6 weeks. Results: While the overall satisfaction of the 218 participants was quite high, there are some points that still need to be addressed in order to ensure a continuing supply of qualified personnel. Among these were economic pressure, work–life balance, work contracts, protected research time, and a demand for an improved curriculum. Conclusion: Mentoring programs, improved education, and strengthening the value of societies in radiation sciences as well as translational approaches and more flexible working arrangements might ensure a high-quality workforce and thus patient care in the future.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Radiation oncology; Radiation research; Translational research; Work conditions; Young workforce

Implementation of Whole Skin Therapy: Dosimetry, Optimization and FMEA Analysis - Shariff, Maya; Lotter, M.; Stillkrieg, W.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Integration of a Halcyon Accelerator with ARIA in a Mosaiq - Environment - Risk Analysis Procedure - Shariff, Maya; Lotter, M.; Lambrecht, U.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Is model-based dose calculation based on cone-beam computed tomography suitable for adaptive treatment planning in brachytherapy? - Karius, Andre; Shariff, Maya; Schaller, Sabrina; Lotter, Michael; Strnad, Vratislav; Lackner, Niklas; Fietkau, Rainer; Bert, Christoph; Merten, Ricarda; Schweizer, Claudia (Strahlentherapie und Onkologie, 2024)
Background and purpose: Model-based dose calculation considering tissue compositions is increasingly being investigated in brachytherapy. The aim of this study was to assess the suitability of modern cone-beam computed tomography (CBCT) imaging compared to conventional computed tomography (CT) scans for this purpose. Materials and methods: By means of a phantom study, we evaluated the CT numbers and electron densities measured using a modern CBCT device as well as a conventional CT scanner for various materials. Based on this, we compared dose calculations (using the TG-43 formalism as well as model-based collapsed cone calculations assuming uniform materials [ACEuniform] and considering CT numbers [ACECT#]) on planning CTs and control CBCTs for patients with cervical and breast cancer as well as phantom-simulated skin cancer cases. Assessing dosimetric deviations between the planning CTs and control CBCTs acquired during the treatment course served to estimate interfractional implant variations. Results: The comparison of ACEuniform–ACECT# deviations between planning CTs and control CBCTs revealed no statistically significant difference for almost all examined dose parameters. Dosimetric deviations between model-based dose calculations and TG-43 were partly significant but of small magnitude (< 10 cGy per fraction). Interfractional dosimetric variations were substantially larger than the dosimetric differences found between the various dose calculation procedures. Conclusion: Model-based dose calculation based on modern CBCT imaging was suitable. However, the found differences between these calculations and the TG-43 formalism should be investigated in dose–outcome analyses. The observed interfractional dosimetric variations revealed the importance of performing treatment quality assurance.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Adaptive radiotherapy; Brachytherapy; Breast cancer; Cervical cancer; Model-based dose calculation

Large-field irradiation techniques in Germany: A DGMP Working Group survey on the current clinical implementation of total body irradiation, total skin irradiation and craniospinal irradiation - Heuchel, Lena; Garbe, Stephan; Lühr, Armin; Shariff, Maya (Zeitschrift für Medizinische Physik, 2024)
In 2023, a Germany-wide survey on the current clinical practice of three different large field irradiation techniques (LFIT), namely total body irradiation (TBI), total skin irradiation (TSI) and craniospinal irradiation (CSI), was conducted covering different aspects of the irradiation process, e.g., the irradiation unit and technique, dosimetrical aspects and treatment planning as well as quality assurance. The responses provided a deep insight into the applied approaches showing a high heterogeneity between participating centers for all three large field irradiation techniques. The highest heterogeneity was found for TBI. Here, differences between centers were found in almost every aspect of the irradiation process, e.g., the irradiation technique, the prescription dose, the spared organs at risk and the applied treatment planning method. For TBI, the only agreement was found in the fractionation scheme (2 Gy/fraction, 2 fractions/day) and the dose reduction to the lung. TSI was the rarest of the three LFITs. For TSI, the only agreement was found in the use of 6 MeV when irradiating with electrons. The reported approaches of CSI were closest to standard radiotherapy, using no CSI-specific irradiation techniques or treatment planning methods. For CSI, the only agreement was found in the prescribed dose to the brain (50 – 60 Gy). When asking for future requirements, participating centers considered the lack of standardization as the most important future challenge and suggested to perform (retrospective) patient studies. The results of such studies can then serve as a basis for new and improved guidelines.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Craniospinal irradiation; Germany-wide survey; Total body irradiation; Total skin irradiation

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Unified risk analysis in radiation therapy - Lohmann, Daniel; Shariff, Maya; Schubert, Philipp; Sauer, Tim-Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: The increasing complexity of new treatment methods as well as the Information Technology (IT) infrastructure within radiotherapy require new methods for risk analysis. This work presents a methodology on how to model the treatment process of radiotherapy in different levels. This subdivision makes it possible to perform workflow-specific risk analysis and to assess the impact of IT risks on the overall treatment workflow. Methods: A Unified Modeling Language (UML) activity diagram is used to model the workflows. The subdivision of the workflows into different levels is done with the help of swim lanes. The model created in this way is exported in an xml-compatible format and stored in a database with the help of a Python program. Results: Based on an existing risk analysis, the workflows CT Appointment, Glioblastoma Multiforme, and Deep Inspiration Breath Hold (DIBH) were modeled in detail. Part of the analysis are automatically generated workflow-specific risk matrices including risks of medical devices incorporated into a specific workflow. In addition, SQL queries allow to quickly retrieve e.g., the details of the medical device network installed in a department. Conclusion: Activity diagrams of UML can be used to model workflows in radiotherapy. Through this, a connection between the different levels of the entire workflow can be established and workflow-specific risk analysis is possible.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Activity diagram; IEC 80001-1; Risk analysis; UML